Tourniquet application in primary total knee arthroplasty for osteoarthritis: A systematic review and meta-analysis of randomized controlled trials - Han, Jinchang; Zhang, Xiao-yu; Mu, Shi-yin; Liu, Shi-long; Cui, Qing-tong; Zhang, Chao; Liu, Ai-feng (Frontiers in Surgery, 2023)
Purpose: To identify of the influence of tourniquet on the blood loss, transfusion requirement, swelling, pain, knee function, range of motion (ROM), operation time, bone cement mantle thickness and complications, in patients operated with TKA. Methods: Two authors independently retrieved PubMed, Embase and CENTRAL to identify eligible RCTs evaluate the effectiveness of tourniquet in TKA. Fixed- (I2<50%) or random-effect (I2>50%) model were selected to perform meta-analysis according to the value of I2. Mean difference (MD), and risk ratio (RR) were selected as the effect sizes for continuous and dichotomous variables, respectively. Results: A total of 29 RCTs, involving 2512 operations (1258 procedures with tourniquet and 1254 procedures without tourniquet), were included, and 18 outcomes were compared. Tourniquet application could significantly decrease intra-operative blood loss (MD=-138.72ml, p<0.001), shorten operation duration (MD=-1.77min, p<0.001), and increase cement mantle thickness (MD=0.17mm, p<0.001). However, it was significantly associated with increased post-operative pain intensity, decreased full ROM/ flexion ROM/ extension ROM, poorer knee function, increased knee swelling, and increased LOS, at several follow-up points (p<0.050). No significant difference was found for post-operative draining volume, total blood loss, transfusion rate, change of Hb level, and risks of DVT and all complications. Conclusions: Tourniquet application could only decrease the intra-operative blood loss, but has no effectiveness on the total blood loss and transfusion requirement. On the contrary, it has reverse effect on the pain score, knee function, ROM, swelling, and length of hospital stay.